RESIKO DAN PERLINDUNGAN HUKUM TERHADAP KEMULYAAN MANUSIA AKIBAT PERKAWINAN LIAR - Suaidi, Suaidi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Marriage is the inner bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the one and only godhead. To ensure happiness in the marital bond, state involvement is necessary. Marriages that are registered with state institutions receive legal protection with various problems arising from marriage such as income and inheritance rights. While marriages that are not registered with state institutions, the consequences do not get legal certainty which results in the unprotection of all rights such as child maintenance if they divorce, inheritance rights and property. The reality is that there are still many marriages that are not registered with state institutions, this will result in legal uncertainty.